Conservation vs divergence in LEAFY and APETALA1 functions between Arabidopsis thaliana and Cardamine hirsuta. Issue 2 (18th January 2017) - Monniaux, Marie; McKim, Sarah M.; Cartolano, Maria; Thévenon, Emmanuel; Parcy, François; Tsiantis, Miltos; Hay, Angela
Summary: A conserved genetic toolkit underlies the development of diverse floral forms among angiosperms. However, the degree of conservation vs divergence in the configuration of these gene regulatory networks is less clear. We addressed this question in a parallel genetic study between the closely related species Arabidopsis thaliana and Cardamine hirsuta . We identified leafy ( lfy ) and apetala1 ( ap1 ) alleles in a mutant screen for floral regulators in C. hirsuta . C. hirsuta lfy mutants showed a complete homeotic conversion of flowers to leafy shoots, mimicking lfy ap1 double mutants in A. thaliana . Through genetic and molecular experiments, we showed that AP1 activation is fully dependent on LFY in C. hirsuta, by contrast to A. thaliana . Additionally, we found that LFY influences heteroblasty in C. hirsuta, such that loss or gain of LFY function affects its progression. Overexpression of UNUSUAL FLORAL ORGANS also alters C. hirsuta leaf shape in an LFY‐dependent manner. We found that LFY and AP1 are conserved floral regulators that act nonredundantly in C. hirsuta, such that LFY has more obvious roles in floral and leaf development in C. hirsuta than in A. thaliana .